2007
DOI: 10.1111/j.1600-0889.2006.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The carbon budget of coarse woody debris in a temperate broad-leaved secondary forest in Japan

Abstract: We evaluated the carbon budget of coarse woody debris (CWD) in a temperate broad‐leaved secondary forest. On the basis of a field survey conducted in 2003, the mass of CWD was estimated at 9.30 tC ha−1, with snags amounting to 60% of the total mass. Mean annual CWD input mass was estimated to be 0.61 tC ha−1 yr−1 by monitoring tree mortality in the forest from 1999 to 2004. We evaluated the CWD decomposition rate as the CO2 evolution rate from CWD by measuring CO2 emissions from 91 CWD samples (RCWD) with a cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
2
48
1
Order By: Relevance
“…In our results, 88% of the difference in R S could be accounted for by the difference in R H , and 71% of the difference in R H could be accounted for by the difference in R LL . Combinatorial analysis of the effects of these substrates, including CWD (Jomura et al 2007) and fine root litter, is required in order to improve estimates of heterotrophic carbon balance in forests. Davidson et al (2006) reported the effect of enzyme activity on the temperature sensitivity of the respiration process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our results, 88% of the difference in R S could be accounted for by the difference in R H , and 71% of the difference in R H could be accounted for by the difference in R LL . Combinatorial analysis of the effects of these substrates, including CWD (Jomura et al 2007) and fine root litter, is required in order to improve estimates of heterotrophic carbon balance in forests. Davidson et al (2006) reported the effect of enzyme activity on the temperature sensitivity of the respiration process.…”
Section: Discussionmentioning
confidence: 99%
“…in this forest to permit measurements of CO 2 flux between the forest ecosystem and the atmosphere . Measurements of foliage CO 2 exchange by dominant species (Q. serrata and I. pedunculosa) , R S Tamai et al 2005), root respiration (R R ) , fine root respiration (Makita et al 2009), and CWD respiration (Jomura et al 2007) have been conducted at this site using chamber methods. Databases of forest inventory, biomass, and production data have been compiled to evaluate the NEE measured at the towers.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…In boreal black spruce fire-chronosequence forests, annual emission of CO 2 from CWD depends highly on the mass of CWD (Bond-Lamberty et al 2003). In one warm temperate forest in the wake of a pine beetle attack, CWD respiration contributed 10-16% of the total heterotrophic respiration (Jomura et al 2007). Previous studies have examined the effect of tree species, wood chemistry and density, and decay class of CWD on respiration rate (Yoneda 1975(Yoneda , 1982Harmon et al 1986;Marra and Edmonds 1994).…”
Section: Introductionmentioning
confidence: 98%
“…The contributions of CO 2 efflux from CWD (i.e., CWD respiration) to ecosystem respiration and forest carbon budgets have been determined in tropical (Chambers et al 2001), temperate (Gough et al 2007;Jomura et al 2007), and boreal (Bond-Lamberty et al 2003) forests on the basis of CWD respiration observations, although CWD is a component that is often overlooked in forest carbon-cycle studies. In tropical forests, annual CWD respiration is comparable in magnitude to that of decomposing fine surface litter in central Amazonian forests (Chambers et al 2001).…”
Section: Introductionmentioning
confidence: 99%